Thai street food and brand image development: an investigation from tourists’ perspective / Yanisa Mitgosoom and Ann Suwaree Ashton - Mitgosoom, Yanisa; Ashton, Ann Suwaree (Faculty of Hotel & Tourism Management, 2019)
The main aim of this research was to develop street food destination brand image by conducting an investigation from a tourist perspective. A qualitative approach was adopted for this study: an investigation of international tourists at China Town, Yaowarat, Thailand. Face-to-face interview was used for the data collecting process while content analysis technique was used to analyze data. A total of 64 participants were interviewed from July to November 2018. The findings revealed that the tourists received information about Yaowarat street food from social media such as TripAdvisor, word of mouth, advertisement, and travel guidebook. The most important things for developing street food destination brand image are: the uniqueness of Thai dishes; the worthiness of the price paid; and the attraction of the food, especially deliciousness. Their main activities are eating and taking photos, sightseeing (walking/seeing interesting things around the street food area), and shopping. The study’s contributions and future research are also provided.